Two-Stage Total Knee Arthroplasty for Prosthetic Joint Infection - Cha, Min Seok (Knee Surg Relat Res, 2015)
PURPOSE: This retrospective review was conducted to identify prognostic factors for two-stage reimplantation for infected total knee arthroplasty (TKA) and the rate of reinfection following revision TKA. MATERIALS AND METHODS: Out of 88 patients diagnosed with post-TKA infection between 1998 and 2011, 76 underwent two-stage reimplantation and were reviewed in this study. The 76 patients were divided into two groups-those who experienced reinfection and those who did not. Comorbidities, culture results, and inflammation indices were analyzed and compared between the two groups. RESULTS: Of the 76 patients who underwent a two-stage reimplantation, 18 (23.7%) experienced reinfection. Patients with more than three comorbidities had significantly higher reinfection rates than those with less than three comorbidities (47.1% vs. 4.8%, p=0.032). The reinfection rate between the culture positive prosthetic joint infection group and the culture negative prosthetic joint infection group was not significantly different (p=0.056). Inflammation indices (erythrocyte sedimentation rate [ESR] and C-reactive protein [CRP]) showed a statistically significant difference between patients with reinfection and those without reinfection at 4 weeks after the first-stage surgery. CONCLUSIONS: Reimplantation must be carefully performed when the risk of reinfection is high, particularly in patients with more than three systemic or local comorbidities and higher inflammation indices (ESR and CRP) prior to revision TKA.